Parity and non-parity determinants of exchange rates in Latin American economies - Ho, Catherine Soke Fun; Syed Mohamed, Mohamed Ariff (Taylor's Business School, Taylor's University, 2014)
This paper reports how non-parity fundamental factors together with parity factors are correlated with exchange rate movements. Seven Latin American countries were included in this study using a selection criterion that for a pair of countries to be included, the pair must have more than 50 per cent of trade with the group chosen. The econometric methods applied are appropriate to this topic and include pooled time series regression and seemingly unrelated regression. The findings show that there is support for short and long-run effects on exchange rates from inflation and interest rates. We entered non-parity factors suggested in recent research reports as likely determinants of the exchange rates, and found four non-parity factors that are significantly correlated with exchange rates and these served as control variables in our test model. Our main result shows that both inflation and interest rates are jointly significant factors in most of the tests. The results appear to suggest that exchange rate research should include both non-parity and parity factors. Only then would the parity factor effects be identifiable as relevant to exchange rate formation.